Thoracic ultrasound in the diagnosis of malignant pleural effusion. - Qureshi, N; Rahman, N; Gleeson, F (2009)
BACKGROUND: Malignant pleural effusion (MPE) is a common clinical problem with described investigation pathways. While thoracic ultrasound (TUS) has been shown to be accurate in pleural fluid detection, its use in the diagnosis of malignant pleural disease has not been assessed. A study was undertaken to assess the diagnostic accuracy of TUS in differentiating malignant and benign pleural disease. METHODS: 52 consecutive patients with suspected MPE underwent TUS and contrast-enhanced CT (CECT). TUS was used to assess pleural surfaces using previously published CT imaging criteria for malignancy, diaphragmatic thickness/nodularity, effusion size/nature and presence of hepatic metastasis (in right-sided effusions). A TUS diagnosis of malignant or benign disease was made blind to clinical data/other investigations by a second blinded operator using anonymised TUS video clips. The TUS diagnosis was compared with the definitive clinical diagnosis and in addition to the diagnosis found at CECT. RESULTS: A definitive malignant diagnosis was based on histocytology (30/33; 91%) and clinical/CT follow-up (3/33; 9%). Benign diagnoses were based on negative histocytology and follow-up over 12 months in 19/19 patients. TUS correctly diagnosed malignancy in 26/33 patients (sensitivity 73%, specificity 100%, positive predictive value 100%, negative predictive value 79%) and benign disease in 19/19. Pleural thickening >1 cm, pleural nodularity and diaphragmatic thickening >7 mm were highly suggestive of malignant disease. CONCLUSION: TUS is useful in differentiating malignant from benign pleural disease in patients presenting with suspected MPE and may become an important adjunct in the diagnostic pathway.